2019
DOI: 10.3389/fpls.2019.00414
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis and Functional Validation of a Brassica oleracea Endochitinase Involved in Resistance to Xanthomonas campestris

Abstract: Black rot is a severe disease caused by the bacterium Xanthomonas campestris pv. campestris (Xcc), which can lead to substantial losses in cruciferous vegetable production worldwide. Although the use of resistant cultivars is the main strategy to control this disease, there are limited sources of resistance. In this study, we used the LC-MS/MS technique to analyze young cabbage leaves and chloroplast-enriched samples at 24 h after infection by Xcc, using both susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 93 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Also, decreased abundance of ubiquitin (to stop the bacteria from using ubiquitination pathway) and malate dehydrogenase (to reduce energy metabolism in the early stage of infection) were found, playing important roles in the resistance mechanisms against Xcc. Proteome analysis of Xccinfected young cabbage leaves and chloroplast-enriched samples of both the susceptible and resistant cultivars revealed the differential abundance of photosynthesis-related proteins in both resistance and susceptible interactions (Santos C. et al, 2019). As…”
Section: Proteomicsmentioning
confidence: 92%
See 3 more Smart Citations
“…Also, decreased abundance of ubiquitin (to stop the bacteria from using ubiquitination pathway) and malate dehydrogenase (to reduce energy metabolism in the early stage of infection) were found, playing important roles in the resistance mechanisms against Xcc. Proteome analysis of Xccinfected young cabbage leaves and chloroplast-enriched samples of both the susceptible and resistant cultivars revealed the differential abundance of photosynthesis-related proteins in both resistance and susceptible interactions (Santos C. et al, 2019). As…”
Section: Proteomicsmentioning
confidence: 92%
“…It has been shown that increased abundance of proteins involved with ABA may favour susceptibility ( Kim et al, 2011 ; Desclos-Theveniau et al, 2012 ). The ABA signalling pathway is manipulated by a type III effector (AvrXccC8004) of Xcc , thereby increasing the ABA levels ( Ho et al, 2013 ) and proteins responsive to ABA ( Santos C. et al, 2019 ) during the infection by Xcc . ABA along with ROS and elicitors of plant defence may stimulate Ca 2+ influx ( Tortosa et al, 2019 ) which may increase Ca 2+ in guard cells prompting stomatal closure ( Klüsener et al, 2002 ).…”
Section: Advances In Omics Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, fewer studies rely on protein–protein interaction (PPI) networks, mainly due to the lack of accurate plant models ( Di Silvestre et al, 2018 ). Nevertheless, the number of studies focusing on high-throughput profiling of plant proteomes ( Vigani et al, 2017 ; Castano-Duque et al, 2018 ; Santos et al, 2019 ), on experimental identification of PPIs ( Senkler et al, 2017 ; Osman et al, 2018 ; Huo et al, 2020 ) or their computational prediction ( Ding and Kihara, 2019 ) are recently increasing. The computational prediction of PPI is usually inferred by transferring interactions from model plant orthologs, like Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%